2016
DOI: 10.1037/pas0000247
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of failing to identify suspect effort in patients undergoing adult attention-deficit/hyperactivity disorder (ADHD) assessment.

Abstract: [Correction Notice: An Erratum for this article was reported in Vol 28(10) of (see record 2016-22725-001). In the article, the penultimate sentence of the abstract should read “These results suggest that a significant percentage of those making a suspect effort will be diagnosed with ADHD using the most commonly employed assessment methods: an interview alone (71%); an interview and ADHD behavior rating scales combined (65%); and an interview, behavior rating scales, and most continuous performance tests combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 59 publications
2
67
0
Order By: Relevance
“…Finally, it is important to acknowledge an additional factor when considering the potential diagnostic utility of EF behavior rating scales in diagnosing adult ADHD. Marshall et al (2016) found young adults exaggerating or faking ADHD symptoms were indistinguishable from those diagnosed with ADHD on the two BDEFS indices considered to be most important in making the diagnosis of ADHD: the summary score and total symptom count.…”
Section: Additional Assessment Measures That Might Improve the Adult mentioning
confidence: 87%
See 3 more Smart Citations
“…Finally, it is important to acknowledge an additional factor when considering the potential diagnostic utility of EF behavior rating scales in diagnosing adult ADHD. Marshall et al (2016) found young adults exaggerating or faking ADHD symptoms were indistinguishable from those diagnosed with ADHD on the two BDEFS indices considered to be most important in making the diagnosis of ADHD: the summary score and total symptom count.…”
Section: Additional Assessment Measures That Might Improve the Adult mentioning
confidence: 87%
“…Pettersson, Soderstrom, and Nilsson (2018) found the aforementioned DIVA had a sensitivity of 90% and specificity of 73%, in a group of adult outpatients presenting for ADHD assessment. Marshall, Hoelzle, Heyerdahl, and Nelson (2016) found that, of 102 patients later diagnosed with ADHD based not only on the interview but additional assessment, 39% had an interview consistent with ADHD, 45% had an indeterminate interview, and 16% had an interview inconsistent with their having this disorder. Those patients with an inconsistent interview but still diagnosed with ADHD had results on multiple behavior rating scales and cognitive tests that provided compelling, substantive evidence of their having ADHD.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated individuals can fake ADHD by underperforming on psychological measures 112 and overreporting symptoms. 117 Some performance validity tests 110 and symptom validity tests 116 may be reasonably effective at discriminating feigned from genuine ADHD, but this issue has not been adequately investigated to date.…”
Section: Methods To Reduce the Nmu Of Stimulantsmentioning
confidence: 99%